Atypical Fibroxanthoma of the Medial Canthus: A Rare Presentation. (June 2013) - Rathore, Deepa; Mohyudin, Mohamed N.; Mehta, Purnima; Ahluwalia, Harpreet S.
ABSTRACT Purpose: Atypical fibroxanthoma (AFX) is an uncommon skin tumour occurring primarily in the head and neck. It has rarely been reported in the periocular region. We report a rare case of atypical fibroxanthoma of the medial canthus. Methods: Clinical and histological findings and management of this case are presented.Results: A 90-year-old Caucasian female had primary excision of a medial canthal mass, which was clinically suspected as basal cell carcinoma by our Plastic surgery colleagues. Histology revealed an atypical fibroxanthoma with incomplete excision, with the tumour involving the deep and peripheral resection margins. Within a few weeks she developed a recurrent mass, which was clinically fixed to deep tissues. She was referred to the Oculoplastic service where she underwent a two-stage excision and reconstruction of the right medial canthus with a full thickness skin graft from her arm. Paraffin fixed sections were used to ensure margin clearance. Conclusion: This case emphasises the importance of a diagnostic biopsy. A panel of immunohistochemical markers is essential to make the correct diagnosis of AFX and distinguish it from malignant fibrohistiocytoma and non-keratin expressing squamous cell carcinoma. It usually follows a benign course, but can occasionally demonstrate aggressive local recurrence as well as distant metastasis. Invasion beyond the dermis and a rapid rate of recurrence are suggestive of a more aggressive clinical course. Paraffin fixed sections are preferred over frozen section techniques for this tumour. Medial canthal AFX has not been reported previously.